Electroanalysis - Brett, Christopher M. A.; Brett, Ana Maria Oliveira (Oxford Oxford University Press, 1998)
This informative text introduces the techniques and areas of application of modern electroanalysis, which has a particularly important role with current environmental concerns, both in the laboratory and in the field. It is a unique self- contained text which starts by describing the basic principles of the necessary electrochemistry and then moves on to electrochemical sensors and their mode of functioning. Potentiometric sensors are described, including many types of selective electrode. Following this, amperometric and voltametric sensors are presented together with the various instrumentation and electrode modification strategies to enhance sensitivity and selectivity. A final chapter shows the range of applications of modern electroanalysis, with particular emphasis on trace species, and indicates future trends. Bibliography is provided to enable the reader to gain a further understanding of the topic through textbooks and specialist research journals. This clear and accessible text will be an invaluable study aid for advanced undergraduates and graduate students of chemistry, biochemistry, chemical technology, industrial chemistry and environmental science. Graduate chemists and biochemists in industry and in analytical laboratories, and students of engineering, pharmacology and related biomedical sciences will also find this book useful.
Keywords: Chemistry -- Electroanalysis